Nutritional characteristics of the soils in the permanent forest study area, Mariupol Forest Research Station - Solomakha, N. G.; Korotkova, T. M.; Kravchenko, V. M.; Ivanicheva, Ye. V. (Forestry and Forest Melioration, 2021)
Introduction The soils of the forest and agrarian experimental sites in the State Enterprise ‘Mariupol Forest Research Station’ have been influenced by the ameliorative system of rare protective forest stands, the history of which is more than 125 years. Therefore, it is urgent to study a current chemical composition of the soils. The aim of the research was to study and analyse chemical characteristics of the soils on the arable land and in the forest shelterbelts in the State Enterprise ‘Mariupol Forest Research Station’ as well as in the farm of the Donetsk Region. Materials and Methods The object of the research was medium-humus chernozems formed on heavy loamy soils under forb-fescue-feather grass vegetation on agricultural land and those under the shelterbelts in studied farms. To do the research, we used field, laboratory-analytical, and statistical methods. A chemical analysis was carried out on 33 soil samples. The forest stands were inspected with commonly accepted methods. The results were analysed by means of statistical methods. Results Inspected field shelterbelts are dominated by Quercus robur L. of 50–126 years old. Their area makes 0.7–3.8 ha; the relative density of stocking is 0.6–0.8. The arable land occupies from 9.8 to 34.0 ha. The forested index of the arable land in SE ‘Mariupol Forest Research Station’ is from 9.0 to 13.9 km·km-2, that of the farm land is 3.2 km·km-2. The highest humus content was found in the soils under field shelterbelts in the permanent forest and agrarian experimental site (8.44–17.36%). It was 5.08–6.96% on the arable land. The difference of average values is 6.06%. This value varies more in the stands than in the field. In the soil of the fields and stands of the farm, the content of humus is about 6.0%. The reduction of humus content in the soil in the fields for 60 years is 0.51–0.82%, in the field shelterbelts it is about 2%. At the studied sites, pH of the soil-water extract for the arable soil is 6.8–7.75 (actual soil acidity) and pH of the salt extract is 5.7–6.8 (exchangeable soil acidity). In the field shelterbelts the values were 6.2–7.75 and 5.25–7.0, respectively. The content of nitrogen and potassium is higher in the shelterbelt soil while that of phosphorus is higher in arable land. Conclusions The highest content of humus was found in the 0–10-cm layer of chernozems under the forest shelterbelts in the permanent forest and agrarian experimental site (from 8.44 to 17.36%); on arable land this value varies from 5.08 to 6.96%. The content of humus in the soils in 92–126-year-old forest shelterbelts (SE ‘Mariupol Forest Research Station’) exceeds the value on arable land by 6.06%. In the soils of the farm, the contents of humus in the field and in the stands do not differ significantly (about 6.0%). There has been a decrease in the content of humus in the soil of some fields of agricultural land (about 1.0%) and forest shelterbelts (about 2%) of the permanent forest and agrarian experimental site for the last 60 years. The soil pH in the sites is mostly neutral. The content of nitrogen and potassium is higher in soils in the shelterbelts, while that of is higher in arable land.